ROLE OF INFORMATIVE-COMMUNICATIVE TECHNOLOGIES IN PROCESS OF FORMATION OF THE SELFEDUCATIONAL COMPETENCE IN TEACHERS OF PRIMARY SCHOOL - Voropay Н.А. (Journal of Information Technologies in Education (ITE), 2012)
One of the promising directions of improving the quality of training future professionals in the Bologna process is the implementation of informative-communicative technologies (ICT) in the educational process of higher education. The article opens the question of the use of informative-communicative technologies in process of formation of the selfeducational competence in teachers of primary school.